Impact Of Special Animal Husbandry Packages Among The Farmers Of Western Zone Of Vidarbha In Maharashtra - Gobade, M.R.; Gobade, R.R.; Pal, V.N.; Shende, P.H.; Patil, A.P.; Suradkar , U.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The present work was undertaken to study the impact of special animal husbandry packages among the farmers of western zone of Vidarbha namely Akola, Buldana and Washim districts in Maharashtra . Under these special packages 122 Holstein Friesian crossbreds and 78 buffaloes were supplied to 10 selected SHG’s having 10 beneficiaries each. On analyzing the results, it was found that majority of the beneficiaries (66%) were found to have a positive impact of special packages in raising the economic status, 66% on improvement in social status, 65% in building of confidence in farmers, 69% as motivation of other farmers to adopt A.H. Enterprises whereas 78% of the beneficiaries were found to have a positive impact of these special packages as a ray of hope for sustainable development.